Modeling English teachers’ intention to use ICT: technology acceptance and TPACK - Cao, Li; Rasul, Mohamad Sattar; Omar, Marlissa; Zulnaidi, Hutkemri (International Journal of Evaluation and Research in Education (IJERE), 2025)
Teachers’ acceptance of technology in the teaching setting is significantly influenced by their behavioral intention to utilize information and communication technology (ICT). A considerable amount of study has been done on the use of ICT in teaching English as a foreign language (EFL). Nevertheless, there exists a significant lack of deep studies among EFL teachers in Chinese vocational colleges. Drawing on the technology acceptance model (TAM) and technological pedagogical content knowledge (TPACK) theoretical frameworks, this current study aimed to ascertain whether EFL teachers’ TPACK levels could predict their intention to adopt ICT. A quantitative study was conducted with the participation of 440 EFL instructors from vocational schools in Shandong Province. The seven components met the scale’s validity and reliability requirements and the partial least squares (PLS) approach was utilized to describe the structural model and examine the relationships among significant components. The findings revealed that EFL teachers’ perceived usefulness (PU), perceived ease of use (PEU), and attitudes towards use (ATCU) significantly impacted their behavioral intention to use (BIU) ICT. Moreover, the TPACK framework exerted a substantial influence on their acceptance of ICT. The study’s findings may provide insights and resources for subsequent theoretical research and teaching approaches centered on enhancing the integration of technology in EFL education.